(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In our study, we used the drug Rexetin in the complex treatment of psoriasis in our work, we treated 28 patients with a diagnosis of vulgar psoriasis. 16 men and 12 women aged 17 to 65 years. The duration of the disease varied from 6 months to 14 years. As a result of our work, the following conclusions were made: traditional treatment of psoriasis with the use of a modern antidepressant-Rexetin led to a faster cure of patients, which may serve as a prospect for the active use of this drug in practical health care.